Effect of Dietary Supplementation of Rhus coriaria Grind Seeds and ‎Exogenous Fibrolytic Enzymes on Some Blood Lipids and Ruminal ‎Fermentation Parameters ‎of Awassi Male Lambs - I Hadi, Lateef; J Al-saadi, Majid (The Iraqi Journal of Veterinary Medicine, 2022)
This study was conducted to assess the potential dietary effect of grind seeds of Rhus coriaria ‎‎(gsRC) with and without exogenous fibrolytic enzymes (EFE) on some lipid profiles ‎and ruminal fermentation characteristics of Awassi male lambs. A total of twenty-four Awassi ‎male lambs weighing 21.56±0.77 kg at 3-4 months of age were randomly divided based on BW ‎into four groups with six animals each. Dietary treatments were provided to lambs for 4 ‎months as follows: control group, fed on a concentrate diet at the rate of 2.5% ‎BW with alfalfa hay daily; gsRC-15 group, fed the control group diet supplemented ‎with 15 g/head dried grind seeds of Rhus coriaria daily with diet; EFE-5 group, fed the control ‎group diet supplemented with ‎‎5 g/head of EFE daily with diet; gsRC-EFE group, fed on the ‎control group diet supplemented with ‎15 g/head‎dried grind seeds of Rhus coriaria and 5 g/head ‎of EFE daily with diet. The results showed that serum cholesterol and triglycerides ‎significantly ‎(P‎‎<0.05) reduced in the treated groups compared to the control group, particularly observed in 3rd and 4th months of the experiment. Comparable results ‎were observed for lambs fed on EFE alone in the 4th month of the study. The treatment groups showed significantly (P‎‎<0.05) lower ruminal pH levels at the beginning, in the middle, and at the end of the experiment. At the middle and end of the study’s last month, the volatile fatty acids (VFAs), ammonia nitrogen (NH3-N), and microflora activity of the rumen were significantly (P‎‎<0.05) higher in the treated groups compared to the control group. It can be ‎concluded that sumac seed powder and EFE can be used in combination or alone as an effective ‎feed additive to improve lipid profiles and rumen fermentation parameters in Awassi male lambs‎‎.